The best american short stories 2022 eaudiobook - Greer, Andrew Sean (Best American Short Stories., 2022)
A collection of the year's best short stories, selected by Pulitzer Prize winner Andrew Sean Greer and series editor Heidi Pitlor. Andrew Sean Greer, "an exceptionally lovely writer, capable of mingling humor with sharp poignancy" (Washington Post), selects twenty stories out of thousands that represent the best examples of the form published the previous year. Supplemental enhancement PDF accompanies the audiobook.